The Influence of Price Perception, Store Atmosphere, and Customer Experience on the Purchase Decision of Mixue Drinks on Jalan Sisingamangaraja, Medan Amplas - Ramadhan Lugu; Rukmini Rukmini; Toni Hidayat; Melissa Zuraini Hasibuan; Muhammad Rizaldy Wibowo (International Journal Business, Management and Innovation Review, 2025)
This research aimed to examine the influence of price perception, store atmosphere, and customer experience on purchasing decisions for Mixue drinks on Jalan Sisingamangaraja Medan Amplas. The population consisted of Mixue customers in the area, with 85 respondents selected using random sampling based on the Slovin formula. Data were analyzed using multiple linear regression with SPSS 25.0. The regression equation derived from the analysis was Y = 5.836 + 0.144 X1 + 0.130 X2 + 0.473 X3 + e, where X1 is price perception, X2 is store atmosphere, and X3 is customer experience. The F value of 5.836 exceeds the F table value of 2.716, indicating that these three variables collectively influence purchasing decisions. Individually, price perception (X1 = 2.288), store atmosphere (X2 = 2.820), and customer experience (X3 = 2.778) all had significant effects, as their t values were greater than the t table value of 1.664. The coefficient of determination (R2) value of 0.570 shows that these three factors together explain 57% of the variation in purchasing decisions for Mixue drinks.